2023
DOI: 10.4103/jhrs.jhrs_143_23
|View full text |Cite
|
Sign up to set email alerts
|

Limited Effects of Ultra-low Oxygen Concentration during Extended Embryo Culture on In vitro Fertilisation Outcomes in Indian Women: A Retrospective Cross-sectional Study

Deven Patel,
R. G. Patel,
Trupti Patel
et al.

Abstract: Background: Amongst various other factors, oxygen (O2) concentration in embryo culture plays an important role in determining pregnancy outcomes in women undergoing in vitro fertilisation. Some studies have reported that lowering O2 levels in embryo culture provides better results. Aims: To explore the effects of low- and ultra-low- O2 concentrations (5% and 2%, respectively) in extended embryo culture on various outcome parameters of pregnancy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Recently, Li et al reported that the biphasic strategy (5-2% O 2 ) resulted in a better blastulation rate for low-quality cleavage embryos, but not for high-quality cleavage embryos [77]. The most recent study is a retrospective cross-sectional one that found only marginal benefits with the biphasic (5-2%) oxygen strategy: they performed both fresh and frozen embryo transfers, finding that there was no difference in the pregnancy and implantation rates although, in fresh embryo transfers, the implantation rate of embryos cultured with the biphasic oxygen strategy was significantly better [78].…”
Section: Culture Of Human Embryos Under Low Oxygen Levelsmentioning
confidence: 99%
“…Recently, Li et al reported that the biphasic strategy (5-2% O 2 ) resulted in a better blastulation rate for low-quality cleavage embryos, but not for high-quality cleavage embryos [77]. The most recent study is a retrospective cross-sectional one that found only marginal benefits with the biphasic (5-2%) oxygen strategy: they performed both fresh and frozen embryo transfers, finding that there was no difference in the pregnancy and implantation rates although, in fresh embryo transfers, the implantation rate of embryos cultured with the biphasic oxygen strategy was significantly better [78].…”
Section: Culture Of Human Embryos Under Low Oxygen Levelsmentioning
confidence: 99%